The Overall Prevalence of Hypothyroidism in Children Suffering Chronic Constipation in Shahrekord in 2019 - Payam Samei; Hassan Talakesh; Alizamen Salehifard Jouneghani; Masoomeh Khaledi Sardashti (Shahrekord University of Medical Sciences, 2022)
Background and aims: Children with thyroid disorders may be significantly exposed to a higher likelihood of constipation; however, the cause of this link remains unclear. The study aimed to assess the prevalence of hypothyroidism in children suffering from chronic constipation. Methods: This cross-sectional study was conducted on 380 infants over 30 days old with chronic constipation. All participants were asked for thyroid-stimulating hormone (TSH) and free T4 tests. Results: The average age of participants was 64.62 ± 37.28 months. The overall hypothyroidism in the study population was estimated to be 4.2% based on the value of measuring serum TSH and 1.0% based on the value of serum-free T4. Further, abnormal values of both serum biomarkers led to the prevalence rate of 0.02% for hypothyroidism. Conclusion: According to the findings, there was a relationship between hypothyroidism and constipation in children; however, this relationship needs further evaluation.